Development of problem-solving skills in medical students. Cienfuegos 2020-2022 - Oramis Isabel Padrón Aguilera; Yolanda Cabrera Macías; Ernesto José López González; María Soledad Vilches León; Fanny Arbolay Sanabria; Walkiria Díaz Senra (Medisur)
Background: the development of problem-solving skills in medical students constitutes a need for the educational teaching process, to contribute to learn to learn ability development. Objective: to identify the development of problem-solving skills in medical students from the Human Ontogeny and SOMA subject. Methods: pedagogical research with sequential explanatory type mixed design. It took place from September 2020 to May 2022 at the Cienfuegos Medical Sciences University. 320 first-year medical students was the universe. The intentional non-probabilistic sample consisted of 58 students. A questionnaire was used to evaluate the learning-to-learn skills training level, observations of teaching activities, documentary review and focus groups. Results: difficulties were identified in the development of problem-solving skills such as deficiencies in the domain of cognitive, procedural knowledge and attitudes, not everyone confronts and relates ideas from basic texts, conferences, complementary materials and the Internet, as well as lack of mastery and depth of your problem-solving skills. Conclusions: the problem solving skill is not properly developed in medical students.